Instrumentos teóricos e técnicas para construção de consenso: Aplicação nas situações e problemas identificados na evolução das negociações do Acordo da ALCA - Área de Livre Comércio das Américas - Gouvêa, Rômulo Lemos de (2005)
The main subject of this study is the analysis of negotiations. The study was developed based on the scenery of paralization and impasse of the negotiations for the Free Trade Area of the Americas - FTAA. Generally speaking, delays and interruptions caused by controversies and impasses end up becoming strong efficiency problems which jeopardize the consensus building during any negotiation. As a justification, the target of this study is to identify processes and recommendations to help obtain, efficiently, agreements in the negotiations. Its final objective was to search for theoretical tools and techniques to be applied in situations of stoppage in a sense of eliminating the difficulties or making them at least easier to deal with. Secondarily other theoretical points of view were considered with the intention of understanding how strategies and theoretical tools can contribute in each situation or in each different scenario of the negotiation. Through the different ways of looking at it for the conduction of the negotiations, for evaluating the dimensions of the negotiations and in order to build up the consensus, the researcher was able to understand the perception and the interpretation of the subject in view. At last the conclusion was that the applicability of the chosen framework is positive in helping solve problems and controversies as well as building up the consensus during the negotiations.